Some Reflections on the Constitutional Review in Albania in a Comparison Key - Tafani, Ismail; Tokrri, Renata (Richtmann Publishing, 2021)
In this study we will try to analyze the foundations of the Constitution as a pillar and as a guarantee for its solidity. The study will also address the need for revision of the constitution as a fundamental element of its existence and continuity. Particular emphasis will be given to the comparison of the constitutions of the most important countries in the world as regards the procedures and limits to the constitutional revision. In this sense, the constitutions of some Balkan Peninsula countries will be analyzed to draw a comparison and analyze the Albanian Constitution as regards the procedure for its revision. The study intends to analyze the procedures for the revision of the Constitution as well as the explicit and implicit limits to these revisions. In the Constitutional revision in Albania in 2016, the role of the Constitutional Court on the control of the constitutional legitimacy of constitutional revision laws was clarified. Formal constitutionality is usually emphasized since the Albanian constitutional reform underlined that the Constitutional Court in Albania could express itself on the constitutionality of the Constitutional revision law only from a formal point of view. Received: 2 January 2021 / Accepted: 27 February 2021 / Published: 7 March 2021